Developing a transformational digital strategy in an SME: The role of responsible management [version 2; peer review: 2 approved] - Joe Morecroft; Paul Levy; Mona Rashidirad (Emerald Publishing, 2022)
Based on the case study of an SME company in the United Kingdom (which we will call SweetStar Cloud), this paper examines the attempts of the company to achieve significant strategic change. The company is attempting to move from being a tradition managed service provider of Information Services towards becoming a significant influencer in the market for digital services in the UK. As part of a Knowledge Transfer Partnership (KTP), a local UK University has been closely involved in developing this new strategic direction and it is well poised to present and analyse the story. From the use of tried and tested strategic tools, including Porter's Generic Strategies and segmentation and targeting, the company has also embraced digital-specific approaches for developing partnerships with clients, developing pilot projects and experimenting with its use of social media. At the heart of this research is an analysis of the move from push marketing towards models of attraction. This paper aims to explore how traditional strategic tools are still applicable in the digital era alongside new tactical approaches in the digital sector. This aim has led to an approach to business that is responsible, in terms of moving away from a traditional push-selling model to one of partnership with customers at a strategic level. Strategy in dynamic markets often highlights responsiveness as a key success factor. The ability to respond (a response-ability) requires more agile companies. As SweetStar Cloud has developed its strategy, it has focused in achieving this more effective ability to respond through a more collaborative approach. In this sense, agile response-ability converges with business responsibility, as new abilities in communication, cooperation and trust development become key.